Kelayakan Tingkat Suku Bunga Kredit Bagi Para Petani : Studi Kasus Desa Mone, Sulawesi Tenggara - Theresia Gunawan (Business Administration Department - Universitas Katolik Parahyangan, 2010)
Having abundant natural resources is not a guaranty for Desa Mone to live in wealth.Even though Desa Mone as one of the biggest and the best producers of mete nuts inIndonesia, many of farmers still live in poverty. In this research, the author want tohelp them in finding the most feasible interest rate for their business.Keywords: Net present value, time value of money, interest rate of return